Efeito da heterogeneidade de habitats na composição e distribuição da assembleia de Chironomidae (Diptera) em riachos preservados de Mata Atlântica, no sul do Brasil - Gurski, Fernanda de Almeida (2011)
The heterogeneity of substrate in streams promotes the colonization and diversity of benthic organisms. Among them, Chironomidae larvae are one of the most abundant in aquatic ecosystems. This study aimed at determining the composition, richness, diversity and the existence of distribution patterns of Chironomidae larvae in different microhabitats of preserved streams of Atlantic Forest. Samplings were performed in February and August 2010, with a Surber-type sampler. The environmental variables analyzed were not significantly different between sampled streams, but the taxonomic richness of Chironomidae larvae was distinct between the microhabitats. In the total, 6,429 Chironomidae larvae were identified and classified into 96 taxa belonging to the subfamilies Chironominae, Tanypodinae and Ortocladiinae. The analyses of density, richness, evenness and diversity, in relation to the months, sites and microhabitats, have pointed out statistically significant differences in the larval distribution for the different microhabitats. Among them, the highest richness was observed in the deposits of litter, and the highest number of exclusive species took place in the pool regions. Thus, the composition and structure of the Chironomidae assemblage is directly related to the availability and heterogeneity of habitats in streams.